Attention Deficit Hyperactivity Disorder in Girls and the Risk of Unplanned Pregnancies - Florina Rad; Alexandra Mariana Buică; Nicolae Gică (Children)
Background/Objectives: Although ADHD in adults has become visible and inclusive in recent years in diagnostic manuals, research is still limited regarding the long-term outcomes of patients with this disorder. The main objective of this research was to address the many facets of predictor variables in girls with ADHD facing unplanned pregnancies at young ages in order to improve the management of pre-, peri-, and postnatal complications that may occur, as well as for early psychiatric diagnosis and effective intervention. Methods: PubMed and Web of Science Databases were used to perform literature research, and a total of 27 records were selected and used for data extraction. Results: Related articles have included the persistence of ADHD symptoms comorbid with other disorders among girls with ADHD as a risk factor for teenage pregnancies. Conduct disorders and substance use disorders are the main co-occurrent diagnoses that increase the likelihood for teenage childbirth. Unplanned pregnancies at young ages are associated with unfavorable psychosocial trajectories both for the mother and the child. Conclusions: In this review, we emphasize the importance of predisposing factors for risky sexual behaviors and unplanned pregnancies in cases of girls with ADHD. The topic of the article draws attention to the need for uniform national individualized care of girls with ADHD, the implementation of programs to prevent academic failure and early parenthood as well as addressing comorbid obstetrical and psychiatric conditions, especially in regions where the rate of adolescent births continues to be high.